Analisis Kemampuan Berpikir Siswa Berdasarkan Teori Van Hiele pada Materi Kubus dan Balok - Hersiyati Palayukan; Evy Lalan Langi; Inelsi Palengka; Lina Rihatul Hima (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
Every student has different abilities, this difference is due to the different stages of ability that students have. The purpose of this study was to describe students' thinking skills based on Van Hiele's learning theory. The subjects of this study were 15 students of class VIII SMPN 2 Makale. The instruments used were test descriptions and interviews. The results showed 93% who had the ability to think at the introductory stage (stage 0), 80% of students who had the ability to think at the stage of analysis (stage 1), 33% of students who had the ability to think at the sequencing stage (stage 2), and 20% of students. who has the ability to think at the deduction stage (stage 3). Thus, the thinking ability of iclass VIII students of SMP Negeri 2 Makale based on Van Hiele's theory on cube and block material reaches stage 3 or the deduction stage.